OPEN INNOVATION MODELS FOR KNOWLEDGE DRIVEN FOOD AND PACKAGING MANUFACTURING. (2014) - Tsimiklis, Panagiotis; Qin, Sheng Feng; Green, Stephen; Rodden, Tom; Baurley, Sharon; Makatsoris, Charalampos
No abstract available